Peningkatan Pertumbuhan dan Produksi Jagung Manis Melalui Penerapan Sistem Pengolahan Tanah dan Pemberian Mulsa pada Lahan - Gribaldi Gribaldi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Tillage and mulching are intended to create good soil conditions which is suitable for plant growth so could increase crop production. This study aims to gain tillage system and the organic mulching which can improve the growth and the production of sweet corn on the dry land. The experimental design used in this study is a randomized block design arranged as factorial with two treatments factors and three replications. The first factor is tillage which consists of no tillage (P0), minimum tillage (P1), and maximum tillage (P2). The second factor is mulching which consists of no mulching (M0), mulching (M1). The results showed that the soil tillage system and mulching affect on growth and production of sweet corn, minimum soil tillage systems and mulching best affect on the growth and production of sweet corn on the dry land.